Aproximações entre o ensino de filosofia e a agroecologia: repensando a questão agrária e o agronegócio no Brasil através da perspectiva histórico-crítica - Figueiroa, Tiê Nogueira (Universidade Federal de São Carlos, 2021)
This paper has as object of study the teaching of philosophy through a critical-philosophical view at the model of the Brazilian rural development in order to discuss and comprehend the relationships between the in natura production method of the food we consume, with the influence of agriculture (and livestock) in the structuring of Brazilian society and its keeping, as well as the impacts on society and the environment. In order to reach this wide objective we are going through the following itinerary: understanding the historic process of land occupation as though as the formation of Brazilian society; comprehending the influence forces of the agribusiness in the different sectors of Brazilian society; thinking about the environmental damage caused by hegemonic agriculture; and offer the agroecology as a solution that also contemplates the need of a land reform; finally, thinking of the philosophy teaching through critical-historical pedagogy as an important part of this process of awareness and politicization of the agriecological questions for a social praxis of high school students. By the end of the research we will offer conclusions referring to the itinerary considering the application of a questionnaire with the students and the practice of this route in the philosophy classes in the Prof. Roque Lelo State School in Caconde-SP.
Aproximaciones entre la enseñanza de la filosofía y la agroecología: repensar la cuestión agraria y la agroindustria en Brasil desde una perspectiva histórico-crítica
Approaches between the teaching of philosophy and agroecology: rethinking the agricultural question and agribusiness in Brazil through a historical-critical perspective
Keywords: Agroecologia; Agronegócio; Ensino de Filosofia; Questão agrária; Reforma agrária; Agroecology; Agribusiness; Philosophy Teaching; Agricultural Question; Land Reform; CIENCIAS HUMANAS